The Sámi: 25 Years of Indigenous Authority in Norway. Issue 1 (1st January 2016) - Falch, Torvald; Selle, Per; Strømsnes, Kristin
Abstract: This article explores the case of the Sámi in the Nordic countries, with a specific focus on the most extensive Sámi political system, that found in Norway. The Norwegian Sámi parliament is an indigenous parliament in a unitary and 'state-friendly' society. As will be seen, that is not an easy position to be in. While most of the Sámi are concentrated in the most northern part of Norway, the Sámi language has a general protection by law. The language has a particularly strong protection within the so-called management area of the Sámi language (which includes 10 out of 428 Norwegian municipalities). The territorial dimension and the strong emphasis upon the traditional Sámi settlement areas are at the core of the Sámi political project. Even so, the Sámi parliament covers the whole of Norway, and a Sámi can register to vote for the Sámi elections independently of where in Norway that person is living. The Sámi are thus an indigenous people, for whom the development of a new public space since the 1980s has as its core the question of ownership of land and water in the key Sámi areas, while the jurisdiction of the Sámi parliament extends not only over the traditional Sámi areas, but also over the whole territory of Norway. The article discusses how this non-territorial model came about and what it implies for the Sámi political project. What kind of boundaries or limits concerning Sámi self-determination and self-rule do we see after 25 years of a Sámi Parliament?